2008
DOI: 10.1007/s11033-008-9307-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-mediated microbubble destruction facilitates gene transfection in rat C6 glioma cells

Abstract: The goal of this study was to determine whether ultrasound (US) exposure combined with microbubble destruction could be used to enhance non-viral gene delivery in rat C6 glioma cells. Microbubbles were prepared and gently mixed with plasmid DNA. The mixture of the DNA and microbubbles was administered to cultured C6 cells under different US/microbubble conditions. Transfection efficiency and cell viability were assessed by FACS analysis, confocal laser scanning microscopy, and Trypan blue staining. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Our experiment showed that TMB assisted gene delivery with ultrasound mediation was able to achieve a gene transfection efficiency of around 43.9%, which was significantly higher than that of the other treatment groups. This result is consistent with previous reports [31,3436]. Interestingly, TMB assisted gene delivery with ultrasound mediation also yielded a significantly higher reporter plasmid expression in comparison with gene delivery with NMBs or without microbubbles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our experiment showed that TMB assisted gene delivery with ultrasound mediation was able to achieve a gene transfection efficiency of around 43.9%, which was significantly higher than that of the other treatment groups. This result is consistent with previous reports [31,3436]. Interestingly, TMB assisted gene delivery with ultrasound mediation also yielded a significantly higher reporter plasmid expression in comparison with gene delivery with NMBs or without microbubbles.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, the emergence of gene therapy has further stimulated the microbubble research for the enhancement of gene delivery efficiency [2831]. The ultrasound-targeted microbubble destruction (UTMD) technique has been developed to facilitate the increased regional uptake of plasmid DNA [1113].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, ultrasound frequencies of 1-3 MHz have been used (11,35). However, the present study used low-frequency (21 kHz) and low-energy ultrasound, which is associate with easy penetration of the organism, less tissue absorption and reduced tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Research analyzing the longitudinal effects of antiangiogenic gene therapy on hepatocellular carcinoma revealed a significant decrease in micro-vessel density and increase in apoptosis using US-stimulated therapy with plasmid compared with plasmid alone (Nie et al 2008). Various other studies have investigated US-stimulated delivery of genetic material in the heart (Bekeredjian et al 2005; Shohet et al 2000; Tsunoda et al 2005), pancreas (Chen et al 2006), skeletal muscle (Wang et al 2005; Zhang et al 2006), kidney (Koike et al 2005), central nervous system (Shimamura et al 2005) and solid tumors (Nie et al 2008; Wang et al 2009; Warram et al 2012). …”
Section: Discussionmentioning
confidence: 99%